Implementasi E-Learning Dalam Meningkatkan Minat Belajar Siswa Di SMA Swasta Santu Xaverius Gunungsitoli - Silvester Tree Doni Waruwu; Sitepanus Zebua; Sergius Lay (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The focus of the research departs from the researcher's concern over the reality of a learning system that is still too teacher-centred. The main problem raised is the low interest of students in learning. The purpose of this research is to explore the extent to which the implementation of e-learning is able to increase students' interest in learning. The research method used is qualitative research. This research was conducted at SMA Swasta Santu Xaverius Gunungsitoli. The research informants were seventeen people as a representation of educational actors in SMA Swasta Santu Xaverius Gunungsitoli. The selection of locations and research subjects was done by purposive sampling. Data analysis used the Miles and Huberman model. The analysis was conducted through three processes, namely: data reduction, data display, and data verification. Based on the research that has been carried out, the research results illustrate that teachers and students have collaborated the e-learning learning system with face-to-face or conventional learning. Through e-learning, teachers and students utilise the internet network to share learning materials, send assignments, and search for additional knowledge through applications or websites. The implementation of e-learning in SMA Swasta Santu Xaverius Gunungsitoli has a positive impact on learning activities. This is evidenced by the increase in students' interest in learning. Suggestion